Gun violence and mental illness - Gold, Liza H. (American Psychiatric Association Publishing, 2016)
Gun violence and serious mental illness / Emma McGinty and Daniel Webster -- Firearms and suicide in the United States / Matthew Miller, Catherine Barber, Deborah Azrael -- Gun violence, urban youth, and mental illness / Carl Bell -- Mass shootings and mental illness / James L. Knoll, IV, George D. Annas -- School shootings and mental illness / Peter Ash -- Mental illness and the national instant criminal background check system / Marilyn Price, Patricia Recupero, Donna Norris -- Mental illness, dangerousness, and involuntary commitment / Eric Drogin and Carol Spaderna -- Accessing mental health care / Robert Trestman, Fred Volkmar, and Liza Gold -- Structured violence risk assessment : implications for preventing gun violence / Daniel C. Murrie -- Suicide and firearms : risk assessment and public policy / Robert I. Simon, Liza H. Gold -- Treatment engagement, access to services and civil commitment reform : would these strategies help reduce firearm-related risks? / Debra A. Pinals -- Preventing gun violence : decreasing access to firearms during times of crisis / Josh Horwitz, Anna Grilley, and Kelly Ward -- Relief from disabilities : mental health evaluations in firearm rights restoration hearings / Liza Gold and Donna Vanderpool -- Decreasing gun violence : social and public health interventions / Shannon Frattaroli, Shani A.L. Buggs